Dual-Energy Computed Tomography for Detection and Characterization of Monosodium Urate, Calcium Pyrophosphate, and Hydroxyapatite: A Phantom Study on Diagnostic Performance. Issue 7 (July 2021) - Døssing, Anna; Müller, Felix Christoph; Becce, Fabio; Stamp, Lisa; Bliddal, Henning; Boesen, Mikael
Abstract : Objectives: The aim of this study was to determine the diagnostic performance of dual-energy computed tomography (DECT) to detect and distinguish crystal deposits in a phantom. The primary objective was to determine the cutoff DECT ratio and the cross-sectional area (CSA) of a crystal deposit necessary to differentiate monosodium urate (MSU), calcium pyrophosphate (CPP), and calcium hydroxyapatite (HA) using DECT. Our secondary objective was to determine the concentration for limit of detection for MSU, CPP, and HA crystal deposits. Exploratory objectives included the comparison between 2 generations of DECT scanners from the same manufacturer as well as different scanner settings. Materials and Methods: We used a cylindrical soft tissue phantom with synthetic MSU, CPP, and HA crystals suspended in resin. Crystal suspension concentration increased with similar attenuation between MSU, CPP, and HA in conventional CT. The phantom was scanned on 2 dual-source DECT scanners, at 2 dose levels and all available tube voltage combinations. Both scanners had a tin (Sn) filter at the high-energy spectra. Dual-energy CT ratios were calculated for a given tube voltage combination by dividing linear regression lines of CT numbers against concentration. Dual-energy CT ratios were compared using an analysis of covariance. Receiver operating characteristic curves and corresponding areas under the curve (AUCs) were calculated for individual crystal suspension comparisons (HA vs CPP, MSU vs CPP, and MSU vs HA). Results: At standard clinical scan settings with 8 mGy and 80/Sn150 kV, the DECT ratios were as follows: CPP, 2.02 (95% confidence interval [CI], 1.98–2.07); HA, 2.00 (95% CI, 1.96–2.05); and MSU, 1.09 (95% CI, 1.06–1.11). Ratios varied numerically depending on the scanner and tube voltage combination. Monosodium urate crystal DECT ratios were significantly different from HA and CPP ( P < 0.001), whereas DECT ratios for HA and CPP crystals did not differ significantly ( P = 0.99). The differentiation of MSU crystals from both calcium crystals (HA and CPP) was excellent with an AUC of 1.00 (95% CI, 1.00–1.00) and an optimal cutoff DECT ratio of 1.43:1.40 depending on the scanner. In addition, differentiation of MSU and calcium-containing crystals (HA and CPP) required a CSA of minimum 4 pixels of crystal at standard clinical scan conditions. In contrast, differentiation between CPP and HA crystals was moderate with AUCs ranging from 0.66 (95% CI, 0.52–0.80) to 0.80 (95% CI, 0.69–0.91) and an optimal cutoff DECT ratio of 2.02:2.06 depending on the scanner. Furthermore, differentiation between CPP and HA crystals required a CSA of minimum 87 pixels of crystal at standard clinical scan conditions, corresponding to a region of interest of 3.7 mm diameter. When scanning at highest possible spectral separation and maximum dose of 50 mGy, the limit of detection for crystals within a region of interest of 50 pixels was 14 mg/cm 3 for MSU and 2 mg/cm 3 for both CPP and HA. Conclusions: This phantom study shows that DECT can be used to detect MSU, CPP, and HA crystal deposits. Differentiation of CPP and HA was not possible in crystals deposits less than 3.7 mm in diameter, but MSU could accurately be differentiated from CPP and HA crystal deposits at standard clinical scan conditions. Abstract : Supplemental digital content is available in the text.